Assessing the Impact of Seven Marketing Mix Elements on Restaurant Businesses: Insights from Online Reviews - Febrian Humaidi Sukmana; Eka Mayani (Universitas Medan Area, 2024)
This study analyzes the significance of the 7P marketing mix elements on customer perceptions and preferences for restaurants, using Google Maps reviews. Descriptive statistics and content analysis were employed to uncover customer perceptions and preferences. By analyzing 686 reviews from Kebalen Cafe, the analysis was conducted in three stages: exploring relationships among review variables, conducting descriptive statistical analysis and word visualization, and performing quantitative content analysis to identify common phrases related to customer experiences. The results indicate that product and price are the most frequently discussed elements, highlighting the importance of food quality and pricing in in-fluencing customer satisfaction. However, other elements such as place, promotion, process, people, and physical evidence received less attention. The implications for restaurant management suggest the need to increase focus on the less emphasized elements to enhance marketing strategies. Theoretically, this re-search contributes to the marketing literature by utilizing customer-generated online reviews to analyze the marketing mix elements that garner greater customer attention. Practically, these findings can serve as a basis for management to improve restaurant operations, particularly in promotion, service process enhancements, employee training, and improving the restaurant's physical appearance to enhance the overall customer experience.